Ginsenosides Regulates Innate Immunity to Affect Immune Microenvironment of AIH Through Hippo-YAP/TAZ Signaling Pathway - Zhang, Kehui; Li, Jiacheng; Shi, Zhe; Zhu, Yingying; Yang, Jing; Liu, Xiaolin; Que, Renye; Lin, Liubing; Chen, Yirong; Li, Yong (Frontiers in Immunology, 2022)
Autoimmune hepatitis (AIH) is characterized by chronic progressive liver inflammatory, which currently lacks safe and effective medicine. Glucocorticoid is still the first choice for the treatment of AIH. Previous studies have confirmed that ginsenosides (GSS) can exert glucocorticoid-like effects and have therapeutic effects on various autoimmune diseases. However, the mechanism of GSS on AIH remains unclear. Bone marrow-derived suppressor cells (MDSC) are an important part of the innate immune system, which has been proved to be an important driver of follow-up acquired immune response in many autoimmune diseases, including AIH. Here, we found that GSS intervention can regulate the immune microenvironment and liver injury induced by Con A in AIH mice. In vitro, we co-cultured MDSCs from healthy mice and T cells from AIH mice, and then intervened with different drugs in an attempt to explore the therapeutic mechanism. The proliferation and differentiation of MDSCs and T cells were analyzed by flow cytometry. GR, Hippo-YAP signal pathway and the expression of MDSC-related genes and proteins were detected by qRT-PCR and Western Blot. The changes of NO and ROS levels were further analyzed. The expression trend of related cytokines (IFN- γ, TGF- β, IL-10, IL-6, IL-17) was detected by ELISA. Furthermore, the ALT and liver pathology of mice were analyzed to evaluate the liver function of mice. We found that MDSCs proliferation was inhibited, and T cells tended to differentiate into Th17 rather than Treg in AIH mice. On the other hand, the intervention of GSS activated GR and Yap, and promoted the proliferation of MDSCs, especially M-MDSCs, which further promoted the differentiation of Treg to establish immune tolerance, and then alleviate the liver injury. Therefore, we propose that GSS can alleviate AIH by modulating the innate immunity and adaptive T cell immunity, which may be an important mechanism of GSS in ameliorating liver injury induced by AIH.